Optimization of Biodiesel Synthesis from Kapok Seed Oil (Ceiba pentandra) through Transesterification Reaction with a TiO2 Catalyst - Rozitawati, Mona; Gunawan, Erin Ryantin; Suhendra, Dedy; Farida Ariani (Jurnal Pijar Mipa, 2025)
Biodiesel represents a renewable, environmentally friendly, and locally producible alternative to conventional diesel fuel. This research synthesized biodiesel from kapok seed oil (Ceiba pentandra) via transesterification using a TiO₂ catalyst, with process parameters optimized to maximize yield. Kapok seed oil was extracted using Soxhlet extraction with n-hexane and purified by vacuum column chromatography. The transesterification process involved systematic variation of the oil-to-methanol molar ratio, catalyst mass, reaction temperature, and reaction time. Optimal conditions were established at a 1:10 molar ratio, 0.20 g of catalyst mass, a reaction temperature of 60 °C, and a reaction time of 90 minutes, resulting in a biodiesel yield of 71.58%. Characterization of the biodiesel revealed a density of 0.88 g/mL, viscosity of 3.10 cSt, acid value of 1.89 mg NaOH/g, and saponification value of 231.879 mg KOH/g. GC-MS analysis identified methyl palmitate, methyl linoleate, and methyl oleate as the principal methyl ester components, with methyl oleate as the predominant species. These findings demonstrate that biodiesel derived from kapok seed oil possesses properties suitable for use as an alternative fuel that meets established quality standards.